Morphometric analysis of Gorontalo (Indonesia) native chickens from six different regions (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sophian A, Abinawanto, Nisa UC, Fadhillah. 2021. Morphometric analysis of Gorontalo (Indonesia) native chickens from six different regions. Biodiversitas 22: 1757-1763. Research on the diversity of Gorontalo native chickens based on morphometric analysis of body weight, leg length, head length, head length to beak and head width was conducted. This study was conducted to identify the diversity of native chickens in six regions spread across Gorontalo Province, Indonesia. The method used in conducting statistical analysis is the principal component analysis (PCA) method. This method was performed to identify which morphometric factors play a role in relationship analysis of Gorontalo native chickens. Based on statistical analysis, it was found that of the 5 variables used in this study, 3 variables had Measure of Sampling Adequacy (MSA) values > 0.5 ranged from 0.537 to 0.648, namely body weight, leg length, and head length. Meanwhile, the other 2 variables, namely Head to Beak Length and Head Width, have MSA values
Keywords: Diversity, Gorontalo, morphometric, native chicken